Statistical analysis of women's FIVB beach volleyball team performance - Giatsis, G.; Papadopoulou, S. D.; Kouloumenta, I. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
win. The purpose of this study was to investigate the differences in playing characteristics between winning and loser teams in FIVB women's BV World Tour matches in Rhodes 2003. The purpose was two-fold: a) to examine the contribution of skill parameters on the total amount of winning and losing points of the teams and b) to determine the best predictor of team win among the selected skill parameters. Methods From the total of 64 matches of the main draw, 63 matches were analyzed. In total, 2665 hours and 5272 points of BV were played in 144 sets. Data collected from the statistical company of Galanis Sports Data S.A. The following data were recorded from each match: General Characteristics of the Match: time duration of each a) set b) match and points of each team per c) set, d) match. Skill Performance: Attack on side-out and counter phase (points and errors), serves (aces, good, and errors), kills, blocks, digs and other errors. The matches were divided into four sub-groups depending on the final score (2-0 and 2-1) and the result of the match (WI: Win or LO: Loss). An independent samples T-test was used in order to compare the differences of the selected technical skills between a) WI2-0 and LO2-0, b) WI2-1 and LO2-1. The statistical significance was set up at .05 level. Furthermore, stepwise discriminant analysis were conducted to determine whish skill(s) contributed significantly to win a match separately to matches with 2-0 and 2-1 score. Results 45 matches finished with a score 2-0 sets (71.4%) while 18 matches finished 2-1 sets (28.6%). The 50.8 percent of the matches included a set with the minimum difference of two points while the 29.9 percent of all sets had the minimum difference of two points. Stepwise disriminant analysis identified the best predictor(s) of a team win among the nine skill parameters in matches with 2-0 score that were counters (.876) and attack errors (.739), while in matches with 2-1 score the best predictor was counters (.897), in order of greater or lesser importance as indicated by the magnitude of the standardized coefficients. Discussion / Conclusions Time duration and score fluctuation of FIVB women's matches were in accordance with other research [3]. Results showed that WI had better performance than LO in 2-0 matches in all parameters except sideouts and serve errors. WI won more points that LO and they had lesser errors. In 2-1 matches, WI had better performance only on counters and good serves. Counters was the best predictor of all parameters for the team win in 2-1 matches. In conclusion, better performance in counters may helped teams to win the matches in the top international level of FIVB women's BV.